2017
DOI: 10.1007/s10067-017-3655-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HLA-B27 in the general population and in patients with axial spondyloarthritis in Saudi Arabia

Abstract: The prevalence of HLA-B27 in the general population and in axial spondyloarthritis (axSpA) patients in Saudi Arabia is unknown. The aim of this study was to evaluate the prevalence of HLA-B27 in these two populations and describe the delay in diagnosis of axSpA patients. The prevalence of HLA-B27 in the general population was evaluated using cord blood and healthy organ transplant donor databases. Data from patients with axSpA were collected retrospectively from five centers. Ankylosing spondylitis (AS) was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
1
18
2
Order By: Relevance
“…However, we searched eligible studies update to November 2016 and our paper has been online on May 2017. But the study reported by Omair et al was Epub ahead of print on July, 2017, so we do not agree the point of this letter [3].…”
mentioning
confidence: 60%
“…However, we searched eligible studies update to November 2016 and our paper has been online on May 2017. But the study reported by Omair et al was Epub ahead of print on July, 2017, so we do not agree the point of this letter [3].…”
mentioning
confidence: 60%
“…Also HLA B27 positivity rates in nraxSpA disease in different ethnic groups are highly variable. Omair et all showed that HLA B27 positivity was found to be 25,9 % in nraxSpA patients in Saudi Arabia [26]. Another study conducted in Sri Lanka, the HLA B27positivity in Spondyloarthritis patients was found to be 22.8 % [27].…”
Section: Discussionmentioning
confidence: 94%
“…The human leukocyte antigens (HLA) B27 gene, the natural function of which is to present intracellular peptides to cytotoxic T lymphocytes, is strongly associated with SpA ( 20 ). The prevalence of HLA-B27 in the general population ranges from around 2 to 6% ( 21 , 22 ), while it reaches 94% in AS ( 20 ). However, in other phenotypes of the SpA spectrum, HLA-B27 can be detected in lower proportions ranging from 30 to 75% ( 20 ).…”
Section: Criteria For Fm and Spa: State Of The Artmentioning
confidence: 99%